Role of Endoplasmic Reticulum Stress, Autophagy, and Inflammation in Cardiovascular Disease - Zhang, Cheng; Syed, Taha Wasim; Liu, Renjing; Yu, Jun (Frontiers in Cardiovascular Medicine, 2017)
Cardiovascular diseases are a class of heart or blood vessels diseases, which are now considered to be the leading cause of death globally. A number of recent studies have reported key roles for inflammation in the progression of diseased vessels and systematic heart failure. In particular, endoplasmic reticulum (ER) stress, which is mechanistically implicated in inflammation and autophagy, has now been associated with pathophysiological states in the cardiovascular system. Autophagy has also been identified as an important process in the progression of multiple cardiovascular diseases such as in atherosclerosis plaque progression and ischemia and/or reperfusion. In light of the above, it has been proposed that a link between inflammation, autophagy, and ER stress may exist that contribute to diseases of the heart and its supporting vessels. This review highlights current knowledge on the crosstalk between these three biological processes, and the potential of targeting this pathway as a therapeutic approach for cardiovascular disorders and its related diseases.